Detection and Identification of Cryptosporidium in Raw Urban Wastewaters Entering the Bu-shehr Coastal Area by Nested-PCR - Farshid Soleimani; Reza Taherkhani; Sina Dobaradaran; Fatemeh Farshadpour; Atefeh Khalili Doroodzani; Marzeah Taherzadeh (Iranian South Medical Journal, 2023)
Background: The protozoan Cryptosporidium is an intestinal pathogenic parasite; are more common in hot climates and places where water and sewage treatment is less effective. The aim of this study was to detect Cryptosporidium in raw urban wastewaters entering the Bushehr coastal area. Materials and Methods: In total, 48 samples of urban raw wastewater samples were collected from 8 stations in winter and summer seasones. Wastewater samples were filtered through a 300 μm sieve to re-move large particles and then on a cellulose acetate membrane with a pore size of 1.2 μm. The filters were scraped and washed with 40 ml of phosphate buffered saline (PBS) containing 0.05% TWEEN and then centrifuged at 5000 rpm for 10 min at 4°C. The freeze-thaw cycles cycles were used for DNA extraction. The level of extracted DNA was measured by NanoDrop (Spectrophotometer, ND1000), and PCR prod-ucts were separated by electrophoresis in 2% agarose gel. Results: PCR analysis showed out of the 48 samples, 17 samples (35.4%) werepositive PCR amplification by nested PCR in the case of Cryptosporidium spp. In total, 11 and 6 samples were positive in the winter and summer seasons, respectively. Conclusion: Local authorities should be aware of probable cryptosporidiosis epidemics between the residents by paying attention to wastewater treatment processes and suitable preventive measures will help reduce the transmission of human and animal cryptosporidiosis.